If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5u + -15 = 9(u + 1) Reorder the terms: -15 + 5u = 9(u + 1) Reorder the terms: -15 + 5u = 9(1 + u) -15 + 5u = (1 * 9 + u * 9) -15 + 5u = (9 + 9u) Solving -15 + 5u = 9 + 9u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-9u' to each side of the equation. -15 + 5u + -9u = 9 + 9u + -9u Combine like terms: 5u + -9u = -4u -15 + -4u = 9 + 9u + -9u Combine like terms: 9u + -9u = 0 -15 + -4u = 9 + 0 -15 + -4u = 9 Add '15' to each side of the equation. -15 + 15 + -4u = 9 + 15 Combine like terms: -15 + 15 = 0 0 + -4u = 9 + 15 -4u = 9 + 15 Combine like terms: 9 + 15 = 24 -4u = 24 Divide each side by '-4'. u = -6 Simplifying u = -6
| 2x+5y=2y+7 | | 20(d-4)+4=8 | | 4(p+8)+4p=4 | | 8-4xb=2xb | | 13=2x-5y | | 3y^2-5y+12=0 | | 5p+6=4p+8 | | -4-2x-6=-8 | | 1.4f+1.1=8 | | 5x-0.06=6x | | xy+3=w+15z | | 3+a=4a | | 6y+7+3y=3(3y-2)+13 | | 7x+7=4x-20 | | (8x-8)2-25=0 | | 6y+7+3y=3 | | x-5+x+.75x+.25x+3=360 | | 3t+7=-2t+27 | | y=-.5(4)-3 | | 6+-5x=-30 | | 16x+7=15+15x | | x-5+x+.75x+.25x+3=180 | | 7-4x-4(x-2)=-1 | | 9-2(x+3)=3 | | (98)x=6272 | | 2x-27=-15 | | 1.75c=7.5 | | 13y+19=6(9+1y)+18 | | y=-.5(2)-3 | | x^2-28x=-49 | | x+102=4*x | | 4-2(5-2x)=9-6x |